PARENTAL CAREGIVER BURDEN FOR CHILDREN WITH ATTENTION DEFICIT HYPERACTIVITY DISORDER AT TERTIARY CARE HOSPITAL IN HYDERABAD - Liaquat, Jahangir; Humayoun, Kazi; Naqvi, Syed Qalb-e-Hyder; Ahemd Abro, Mukhtar; Ahmed, Touseef; Khan Laghari, Darya (Journal of Pakistan Psychiatric Society, 2023)